Effective elimination of dabigatran by haemodialysis - Khadzhynov, Dmytro; Wagner, Frank; Formella, Stephan; Wiegert, Erol; Moschetti, Viktoria; Slowinski, Torsten; Neumayer, Hans-H.; Liesenfeld, Karl-Heinz; Lehr, Thorsten; Härtter, Sebastian; Friedman, Jeffrey; Peters, Harm; Clemens, Andreas (Thrombosis and Haemostasis, 2013)
Dabigatran, a specific, reversible direct thrombin inhibitor, is used to prevent ischaemic and haemorrhagic strokes in patients with atrial fibrillation. As with every anticoagulant, there is a need to rapidly reverse its effects in emergency situations. In an open-label, single-centre phase I study with two fixed multiple dosing periods, we investigated the pharmacokinetics, pharmacodynamics and safety of dabigatran before, during and after 4 hour haemodialysis sessions with either 200 or 400 ml/min targeted blood flow in seven end-stage renal disease patients without atrial fibrillation. Dabigatran was administered over three days in a regimen designed to achieve peak plasma concentrations comparable to those observed in atrial fibrillation patients receiving 150 mg b.i.d. and to attain adequate distribution of dabigatran in the central and peripheral compartments. Plasma concentration-time profiles were similar in both periods on Day 3 (Cmax: 176 and 159 ng/ml). Four hours of haemodialysis removed 48.8% and 59.3% of total dabigatran from the central compartment with 200 and 400 ml/minute targeted blood flow, respectively. The anticoagulant activity of dabigatran was linearly related to its plasma levels. There was a minor redistribution of dabigatran (<16%) after the end of the haemodialysis session. In conclusion, a 4 hour haemodialysis session can rapidly eliminate a substantial amount of dabigatran from the central compartment with a concomitant marked reduction in its anticoagulant activity. There was a clinically negligible redistribution of dabigatran after haemodialysis. These results demonstrate that haemodialysis can be a suitable approach to eliminate dabigatran in emergency situations.
Keywords: Dabigatran etexilate; direct thrombin inhibitor (DTI); pharmacokinetics; elimination; haemodialysis